Food insecurity and perceived effects of COVID-19 on livelihoods in rural Sri Lanka - Singh, Nishmeet; Scott, Samuel P.; Kumar, Neha; Ramani, Gayathri V.; Marshall, Quinn; Sinclair, Kate; Kalupahana, Saman; Fernando, Malika; Silva, Renuka; Perera, Amila; Jayatissa, Renuka; Olney, Deanna K. (SAGE Publications, 2023)
Background: Little is known about how the COVID-19 pandemic has affected food security and livelihoods in Sri Lanka. Objective: This article aims to assess food insecurity, perceived effects of COVID-19, and coping mechanisms among agriculture-based households in rural Sri Lanka. Methods: We used 2 rounds of panel data from phone surveys (n = 1057 households) conducted in 5 districts. Food insecurity (30-day recall), perceived impacts of COVID-19 (6-month recall), and coping mechanisms (6-month recall) were assessed using a household questionnaire. To assess food insecurity, we used the 8-item Food Insecurity Experience Scale. We tested for differences between T1 (baseline: December 2020-February 2021) and T2 (follow-up: July 2021-September 2021) and explored the association between food insecurity and the perceived effect of COVID-19 on income using a logistic regression model. Results: Food insecurity was highly prevalent (T1: 75%, T2: 80%) but varied across districts. Most respondents were affected by COVID-19 and/or COVID-19-associated mitigation measures (T1: 84%, T2: 89%). Among affected households, commonly reported impacts included those on income (T1: 77%, T2: 76%), food costs (T1: 84%, T2: 83%), and travel (∼90% in both rounds). Agricultural activities were also adversely affected (T1: 64%, T2: 69%). About half of COVID-19-affected households reported selling livestock or assets to meet basic needs. Households whose income was impacted by COVID-19 were more likely to be food insecure (adjusted odds ratio: 2.56, P < .001). Conclusions: Households in rural Sri Lanka experienced food insecurity and livelihood disturbances during the COVID-19 pandemic. Additional surveys are needed to assess recovery post-COVID-19 and to understand if programs that support livelihoods have been protective.